Evaluación de los procesos de inscripción y reinscripción para la obtención de registro sanitario en una droguería nacional periodo abril 2017 – abril 2018 - Polo Gómez, Ayde Marisol (2019)
This report on pre-professional practices was carried out with the objective of evaluating the registration and re-registration processes for obtaining sanitary registration in a national drugstore, submitted through the Single Window of Foreign Trade (VUCE) from April 2017 - April 2018, the Information processing was represented by graphic data and tables, evidencing as main feature the breach in the evaluation time and the use of the regulations in force in our country, which despite clear and defined provisions are not applied in a homogeneous manner by of evaluators resident in the General Directorate of Drugs, Supplies and Drugs, generating a delay both in the evaluation of dossiers and in the approval of the product. That is why it is necessary to evaluate the time it takes to review a dossier and therefore the issuance of the respective directive resolution for different products. It was concluded that none of the times established by our authority for pharmaceutical products and medical devices was met